SPECIFICS AND WAYS OF DEVELOPMENT OF ENTERPRISE INTEGRATION IN THE FORMER SOVIET UNION - Еlena А. Hudorenko (Статистика и экономика, 2016)
The article is focused on problems and futuredevelopment of integration processes in thepost-Soviet space. The author highlightssome of the key factors contributing to thedevelopment of centripetal and centrifugaltrends of the region. Special attention isgiven to the industrial policy of countriesinvolved in integration processes. The paper analyzes the role and importance of corporate integration as well as discovers ways ofits development.